Intelligent Security System in A Campus Building Using RFID to Improve Security for Elevator Users - Desmira, D.; Hamid, Mustofa Abi; Noviawati, Lilis; Munandar, Tb. Ai; Martias, M.; Aribowo, Didik (Elinvo (Electronics, Informatics, and Vocational Education), 2023)
This study aims to develop an intelligent system of elevator access with RFID (Radio Frequency Identification) using fuzzy logic as an intelligent system, a safety controller of elevator doors that will open when the power goes out. This research made an Arduino Uno-based elevator access system with an RFID card using fuzzy logic as an intelligence system and markers for each floor. Each floor has an RFID card that contains the information data of each floor.  This research uses research and development (R&D) methods with a waterfall development model. The research procedure consists of several stages, namely the requirement analysis stage, design, implementation, testing, operation, and maintenance. Based on the research and development of the elevator control intelligent system, it can be concluded that the intelligent control lift system was developed using a waterfall model. integration and system testing includes RFID-RC522 reading distance testing, component function testing, and RFID response time measurement testing. The test results show that the RFID-RC522 is readable, and the RFID response time is fast. In addition, the components and all features function well as an elevator control system.